The hidden heterogeneity of inflation and interest rate expectations: The role of preferences - Lena Dräger; Michael Lamla; Damjan Pfajfar (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2021)
Using a new consumer survey dataset, we study the role of macroeconomic preferences for expectations and economic decisions. While household expectations are inversely related to preferences, households with the same in ation expectations can differently assess whether the level of expected in ation and of nominal interest rates is appropriate or too high/too low. This 'hidden heterogeneity' in expectations is correlated with sociodemographic characteristics and affects current and planned spending via the intertemporal elasticity of substitution. We also show that the variation in preferences can be explained with risk preferences. Overall, this adds a new dimension to the definition of anchored expectations.
Keywords: E31; E52; E58; D84; 330; macroeconomic expectations; monetary policy perceptions; ination and interest rate preferences; risk preferences; survey microdata